An in vitro protocol to assay mRNA translation inhibitors using the fluorescent assembly of the split-GFP - Quiroz-Huanca, Ana (2024)
Here, we present an in vitro protocol to assay mRNA translation inhibitors using the fluorescent assembly of split-GFP for translation test (FAST), based on the small fragment GFP11 binding to GFP1-10fast. We detail the expression and purification of the GFP1-10fast protein, DNA template amplification, in vitro GFP11-tagged CspA synthesis, FAST detection of the GFP11-tagged protein, and optional recovery of the fluorescent complex. In vitro synthesis of GFP11 maximizes the molar yield of synthesized proteins, providing enhanced sensitivity to test translation inhibitors. For complete details on the use and execution of this protocol, please refer to Pham et al.